Impact of COVID-19 pandemic on immunisation services performance in Sharqat, Saladin Governorate, Iraq - Muna Abdul Kadhum Zeidan; Suhair Mohammed Hassoon (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the frequency of vaccination delays and the causes of such delays during the coronavirus disease-2019 pandemic. Method: The cross-sectional study was conducted from December 15, 2020, to July 20, 2021, at health centres in the Sharqat area of Saladin Governorate in Iraq, and comprised parents who brought their child for immunisation during coronavirus disease-2019 pandemic. Data was gathered via direct interviews using a pre-designed questionnaire. Data was analysed using SPSS 19. Results: Of the 150 respondents, 84(56%) were from urban areas, and 65(42%) had higher education levels. The association was significant with level of education, socio-economic status of the family and availability of transportation (p<0.05). Conclusion: The vaccination process got disrupted during the coronavirus disease-2019 pandemic in Iraq. Keywords: COVID-19, Pandemic, Immunisation, Performance.